The Tadpole of Vitreorana oyampiensis (Anura, Centrolenidae) in Central Amazonia, Brazil - Menin, Marcelo; Lima, Albertina P.; Rodrigues, Domingos J. (Zootaxa, 2009)
The family Centrolenidae contains about 148 species (Frost 2009), 11 genera and two subfamilies, distributed from southern Mexico to Panama, through the Andes from Venezuela to Bolivia, with species in the Amazon and Orinoco river basins, the Guiana Shield region, and the Atlantic forests of southeastern Brazil and northeastern Argentina (Guayasamin et al. 2009). The subfamily Centroleninae contains nine genera (Centrolene, Chimerella, Cochranella, Espadarana, Nymphargus, Rulyrana, Sachatamia, Teratohyla, and Vitreorana; Guayasamin et al. 2009). In spite of the high diversity in this subfamily, only the larvae of 15 species are well known (Centrolene altitudinale, C. daidaleum, C. geckoideum, C. hesperium, C. venezuelense, Cochranella granulosa, Espadarana andinum, E. prosoblepon, Teratohyla midas, T. pulverata, T. spinosa, Vitreorana castroviejoi, V. eurygnatha, V. helenae, and V. uranoscopa - Starret 1960; Duellman 1978; Heyer 1985; Cadle & McDiarmid 1990; Mijares-Urrutia 1990; Rada de Matinez 1990; Rueda-Almonacid 1994; Hoffmann 2004; Señaris & Ayarzagüena 2005; Rada et al. 2007). Thirteen of them are associated with Amazonian forests or forested slopes of the Andes (Frost 2009). The tadpole of Vitreorana oyampiensis (=Cochranella oyampiensis) has not been formally described; it was mentioned briefly (diagrammatic drawings and larval color notes) in Hero´s tadpole identification key from Central Amazonia (Hero 1990). In this paper we describe the tadpoles of V. oyampiensis and also provide comments on the spawning sites, clutch size, breeding periods and development site of tadpoles.